Pidana Cambuk Terhadap Pelaku Tindak Pidana Maisir di Wilayah Hukum Aceh - Radian Putra; Madiasa Ablisar; Muhammad Ekaputra; Sutiarnoto Sutiarnoto (Universitas Sumatera Utara, 2019)
Abstract. In Indonesia, Aceh is the only province or territory to which makes the Islamic legal norms into Qanun, which applies since the year 2003. Qanun is meant is 12/2003 Number of Alcohol Qanun, Qanun 13/2003 Number of Maisir, Qanun and 14/2003 Number of Seclusion. The third position is legally the qanun is getting sturdier after the promulgation of Act No. 11/2006 of the Government of Aceh (BAL). Then the third the Qanun was replaced with the 6 year Number 2014 Qanun About Jinayat. Among the powers granted to Aceh by the legislation in the field of criminal law is the authority to include basic, forms, levels, limits, properties, and equality between different criminal legislation in force in Indonesia. The form of punishment whip was a form of punishment in the new legislation expected Indonesia could reduce the crime rate or breach of Shari'ah in Aceh. The principle of Islamic law in fact Jinayah him include the management and those settings is to create a sense of security and benefit for the community as well as the certainty of his upright God's law in the Earth Kingdom. Although the implementation of Islamic Sharia in Aceh is far from pristine, but the business as well as the wishes of the people of Aceh for safely syari'atau has reached the point of light and progress gradually, although it is indeed very difficult to run it kaffah . There is a fundamental difference against the application of the penalty of flogging in Aceh with the application of the penalty of flogging according to jinayah i.e. in terms of the number of lashes. This difference is caused due to the application of Islamic Sharia in Aceh has not fully reference such as what is taught in the religion and Islamic Sharia in Aceh implementation is done gradually and still in testing or rudimentary Keywords: Qanun, A Criminal Offence, Maisir